Development of Prayers and Dhikrs Before Sleep Application for Student - Zainuddin, Muhammad Hariz; Sari, Suhaila; Md Taujuddin, Nik Shahidah Afifi; Hazli, Roslan; Idris, Mahamat (Evolution in Electrical and Electronic Engineering, 2021)
Prayers and dhikrs are a very noble worship that calms the spirit and provides the perpetrator with exceptional benefits both in this life and in the hereafter. The project is to develop iOS-based and Android-based applications for prayers and dhikrs, focusing on university students. The Graphic User Interface (GUI) for the applications development is implemented using the Visual Studio Code (VSC) software. The analysis of effects of practicing recital by using the applications is based on the respondents’ experience during the indicated period of time. The performance review survey data result shows, most of the respondents believed the applications can be used continuously for long terms and respondents felt an improvement in their sleep quality, where 45% reported their sleep quality have improved significantly. Moreover, 60% of the respondents agreed that the applications are highly user-friendly to use. This project has successfully achieved its goal as the developed GUI for visual layout and functions for the Prayers and Dhikrs before Sleep recital.